Improved corrosion resistance and biocompatibility of biomedical magnesium alloy with polypeptide TK14 functionalised hydrophobic coating. Issue 1 (6th June 2021) - Shen, Yang; Shen, Xiaolong; Zhang, Hao; Li, Xin; Shang, Tengda; Zhao, Yuancong; Wang, Jin; Huang, Nan
Abstract: Magnesium (Mg) and its alloys can be used as biomedical materials because of their excellent mechanical properties and biocompatibility. However, the rapid degradation rate of Mg‐based materials limits their application in biodegradable intravascular stents. To overcome this issue, we constructed a hydrophobic coating on magnesium. After pre‐treatments with alkali and a silane coupling agent of pure magnesium, 4, 4'‐diphenylmethane‐diisocyanate (MDI) and amino‐terminated polydimethylsiloxane (H2 N–PDMS–NH2 ) were stepwise deposited on the surface, forming an amino‐containing hydrophobic coating (–(M/P)3 ) to enhance the corrosion resistance. Furthermore, polypeptide TK14 was immobilised on the hydrophobic coating to promote vascular endothelial cell adhesion and proliferation. The electrochemical results revealed that the self‐corrosion current density ( i corr ) of –(M/P)3 decreased by approximately 4.5 orders of magnitude compared with that of pure Mg. After TK14 immobilisation, the number of endothelial cells adhering to the surface of –(M/P)3 –T increased significantly. Although the corrosion resistance of –(M/P)3 –T was slightly reduced, the subcutaneous implantation inflammatory response of the surrounding tissues was lower, showing suitable biocompatibility. Therefore, the polypeptide TK14 functionalised hydrophobic coating may be a promising candidate material for the interface of magnesium‐based cardiovascular implants.